Where are you now? : a novel - Clark, Mary Higgins (Simon & Schuster, 2008)
Driven to solve the mystery of her older brother's disappearance ten years earlier, a young lawyer investigates a bizarre community of people who choose to disappear, embarking on a quest with life-threatening consequences.